Respiratory motion during 90Yttrium PET contributes to underestimation of tumor dose and overestimation of normal liver tissue dose. (February 2018) - Ausland, Line; Revheim, Mona-Elisabeth; Skretting, Arne; Stokke, Caroline
Background: Yttrium-90 dosimetry after radioembolization is reliant on accurate quantitative imaging of the microsphere deposition. Previous studies have focused on the correction of geometrical resolution effects. Purpose: To uncover additional effects of respiratory motion. Material and Methods: Mathematical models describing spherical tumors were formed and two blurring effects, limited geometrical resolution and respiratory motion, were simulated. The virtual images were used as basis for dose volume histogram estimations by convolving the radioactivity representations with a dose point kernel. Results: For respiratory motion only, the largest errors were found for the smallest tumors and/or tumors with heterogeneous distribution of yttrium-90 microspheres. The deviations in max dose and dose to 25% and 50% of the tumor volume were estimated at 20–40%, 10–30%, and 0–30%, respectively. Additional blurring from geometrical resolution increased the errors to 55–75%, 50–60%, and 25–60%, respectively. Conclusion: Respiratory motion contributes to underestimation of tumor dose and overestimation of normal tissue dose.